2011
DOI: 10.1177/1044207311407917
|View full text |Cite
|
Sign up to set email alerts
|

Federal Policy on Disproportionality in Special Education

Abstract: Monitoring requirements in the 1997 amendments to and 2004 reauthorization of the Individuals with Disabilities Education Act (IDEA) acknowledged the existence and extent of racial/ethnic disproportionality in special education, especially when, in 2004, Congress designated this concern among the top three priority areas for monitoring and enforcement of the law. However, federal interpretations of the 2004 requirements have created confusion at the State (SEA) and Local Education Agency (LEA) levels. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 9 publications
0
76
0
Order By: Relevance
“…Yet despite the existence of policies intent on remediating the "previous wrongs" of education inequities, particularly for students with disabilities, many remain obdurate (Albrecht, Skiba, Losen, Chung, & Middelberg, 2012;Artiles, 2011). While this list is not exhaustive, students with disabilities who are also students of color and/or English language learners continue to progress academically at rates slower than non-disabled peers, graduate from high school and attend post-secondary education at lower rates, and are disproportionately placed within more restrictive educational placements than peers.…”
Section: Special Education Policy and Equity Concernsmentioning
confidence: 97%
“…Yet despite the existence of policies intent on remediating the "previous wrongs" of education inequities, particularly for students with disabilities, many remain obdurate (Albrecht, Skiba, Losen, Chung, & Middelberg, 2012;Artiles, 2011). While this list is not exhaustive, students with disabilities who are also students of color and/or English language learners continue to progress academically at rates slower than non-disabled peers, graduate from high school and attend post-secondary education at lower rates, and are disproportionately placed within more restrictive educational placements than peers.…”
Section: Special Education Policy and Equity Concernsmentioning
confidence: 97%
“…5 Several problems concerning the efficacy of the indicators may result in the ED's inability to monitor special education implementation. A analysis of SPP/APR data found that even though high levels of disproportionality remained constant across the nation for decades (discussed in next section), most SEAs identify few or no districts with disproportionality that used inappropriate identification practices (Albrecht, Skiba, Losen, Chung, & Middelberg, 2012). In 2005 and 2006, TEA reported only 2% and 0.16% of districts, respectively, with disproportionate representation of racial and ethnic groups in special education and related services that were the result of inappropriate identification (Indicator 9 and 10) (see OSEP, 2018).…”
Section: State Accountability and Special Educationmentioning
confidence: 99%
“…The federal government is currently considering enacting further compliance monitoring policies (Government Accountability Office, 2013; U.S. Department of Education, 2014). Calls are also being made to strengthen existing monitoring policies (Skiba, Albrech, & Lorsen, 2013) including requiring LEAs to report any disproportionality instead of reporting disproportionality resulting only from incorrectly applied procedures or policies (Albrecht, Skiba, Losen, Chung, & Middelberg, 2012). …”
mentioning
confidence: 99%